Wing-tip Vortex Structure and Wandering - Pentelow, Steffen L. (Université d'Ottawa / University of Ottawa, 2014)
An isolated wing-tip vortex from a square-tipped NACA 0012 wing at an angle of attack of 5 degrees was studied in a water tunnel at a chord based Reynolds number of approximately 24000. Measurements were taken using stereo particle image velocimetry at three measurement planes downstream of the wing under each of three freestream turbulence conditions. The amplitude of wandering of the vortex axis increased with increasing distance downstream of the wing and with increasing freestream turbulence intensity. The magnitude of the peak azimuthal velocity decreased with increasing distance from the wing as well as with increases in the freestream turbulence intensity. The streamwise velocity in the vortex core was less than the freestream velocity in all cases. Time resolved histories of the instantaneous waveform shape and location of the vortex axis were determined from sequences of images of fluorescent dye released from the wing.
Keywords: wing-tip vortex; trailing vortex; fluid dynamics; stereo particle image velocimetry; laser induced fluorescence; dye visualization; vortex wandering; vortex axis identification; vortex velocity profile; grid generated turbulence